2020
DOI: 10.1093/cid/ciaa1244
|View full text |Cite
|
Sign up to set email alerts
|

First Real-world Evidence of Meningococcal Group B Vaccine, 4CMenB, Protection Against Meningococcal Group W Disease: Prospective Enhanced National Surveillance, England

Abstract: BACKGROUND 4CMenB is a protein-based meningococcal group B vaccine but the vaccine antigens may also be present on non-group B meningococci. In September 2015, the UK implemented 4CMenB into the national infant immunisation programme, alongside an emergency adolescent meningococcal ACWY (MenACWY) programme to control a national outbreak of group W (MenW) disease caused by a hypervirulent strain belonging to the ST11 clonal complex. The adolescent programme aimed to provide direct protection f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 31 publications
0
49
0
Order By: Relevance
“…The 4CMenB program prevented 98 cases of MenW IMD in infants and young children over the first 4 years. 54 These observations are supported by 2 in vitro studies; high levels of bactericidal activity against 6 clinical MenW isolates from England and Wales in sera from 4CMenB-vaccinated individuals, suggesting cross-reactivity due to surface proteins common to both serogroups. 52 A study with sera from 4CMenB-vaccinated infants demonstrated bactericidal killing of 74% of a panel of MenC, MenW and MenY clinical isolates representing a range of clonal complexes.…”
Section: Non-menb Effects: Potential Protection Of 4cmenb On Serogroup W (Menw) Imd In the Ukmentioning
confidence: 75%
See 1 more Smart Citation
“…The 4CMenB program prevented 98 cases of MenW IMD in infants and young children over the first 4 years. 54 These observations are supported by 2 in vitro studies; high levels of bactericidal activity against 6 clinical MenW isolates from England and Wales in sera from 4CMenB-vaccinated individuals, suggesting cross-reactivity due to surface proteins common to both serogroups. 52 A study with sera from 4CMenB-vaccinated infants demonstrated bactericidal killing of 74% of a panel of MenC, MenW and MenY clinical isolates representing a range of clonal complexes.…”
Section: Non-menb Effects: Potential Protection Of 4cmenb On Serogroup W (Menw) Imd In the Ukmentioning
confidence: 75%
“…77 4CMenB also demonstrates a statistically significant impact in preventing MenW IMD. 54 The potentially wider impacts of 4CMenB on non-MenB/non-MenW disease have yet to be quantified. Of particular interest is whether 4CMenB can also prevent infections due to N. gonorrhoeae which shares 80-90% genetic homology with MenB.…”
Section: Article In Pressmentioning
confidence: 99%
“…Guideline development and revision should also be considered frequently within a global context, ideally with the introduction of new vaccines or vaccination programs, as it becomes increasingly evident that inconsistent management of an infectious disease, either within or between country jurisdictions, can hinder effective disease management. Although conjugate meningococcal vaccines show evidence of reduction in transmission [ 13 ], they do not affect overall carriage rates [ 40 ]. As new vaccines are developed and implemented in population-wide programs, guidelines for management of contacts need to be reviewed to ensure they remain contemporaneous.…”
Section: Discussionmentioning
confidence: 99%
“…IMD is a severe disease caused by Neisseria meningitidis ( N. meningitidis ), a bacteria found in the human nasopharyngeal mucosa, the cells lining the back of the nose and throat [ 5 ]. The disease has a rapid onset and cases require prompt antibiotic treatment to prevent mortality [ 12 , 13 ]. Survivors of IMD often suffer from serious long-term sequalae, including - but not limited to - loss of limbs, neurological damage, hearing loss and physical or psychological scarring [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation